Konsentrasi Pelilinan Terhadap Daya Simpan Buah Pepaya (Carica papaya L.) - Krisdianto Krisdianto; Yusmaidar Sepriani; Badrul Ainy Dalimunthe (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2021)
Post-harvest technology for agricultural products has grown from time to time. One of the post-harvest technologies for agricultural products that is carried out is adding a coating material to the fruit to slow down evapotranspiration which increases the shelf life of papaya fruit. Papaya yields are increasing from time to time, this must be followed by handling the papaya harvest properly. This study aims to determine whether or not the effect of giving wax with oleic acid and tritenolamine solvents on the shelf life of papaya fruit and to determine the concentration of beeswax with oleic acid and tritenolamine solvents which are good for coating papaya fruit. The treatment parameters were wax coating with a concentration of 2%, 4%, 6% and control. Observations included fruit weight, fruit weight loss, fruit texture and organoleptic tests on fruit color, fruit aroma and fruit taste. The results showed that applying beeswax coating with oleic acid and tritenolamine solvent did not affect the shelf life of papaya fruit. The right concentration to coat the papaya fruit is wax coating with a concentration of 4%. Key words: Papaya fruit, wax coating, oleic acid, tritenolamine, shelf life, fruit quality